Current trends of clinical trials involving CRISPR/Cas systems - Zhang, Songyang; Wang, Yidi; Mao, Dezhi; Wang, Yue; Zhang, Hong; Pan, Yihan; Wang, Yuezeng; Teng, Shuzhi; Huang, Ping (Frontiers in Medicine, 2023)
The CRISPR/Cas9 system is a powerful genome editing tool that has made enormous impacts on next-generation molecular diagnostics and therapeutics, especially for genetic disorders that traditional therapies cannot cure. Currently, CRISPR-based gene editing is widely applied in basic, preclinical, and clinical studies. In this review, we attempt to identify trends in clinical studies involving CRISPR techniques to gain insights into the improvement and contribution of CRISPR/Cas technologies compared to traditional modified modalities. The review of clinical trials is focused on the applications of the CRISPR/Cas systems in the treatment of cancer, hematological, endocrine, and immune system diseases, as well as in diagnostics. The scientific basis underlined is analyzed. In addition, the challenges of CRISPR application in disease therapies and recent advances that expand and improve CRISPR applications in precision medicine are discussed.